Long non-coding RNA long intergenic non-coding 00641 mediates cell progression with stimulating cisplatin-resistance in osteosarcoma cells via microRNA-320d/myeloid cell leukemia-1 axis. Issue 3 (1st March 2022) - Tang, JinShan; Zhu, ZiQiang; Dong, Suwei; Wang, YunQing; Wang, JianQang; Chen, HongLiang; Duan, Gang
ABSTRACT: As a staple chemotherapy medicine, cisplatin (DDP) is extensively applied in cancer patients, but its drug resistance is limited. Numerous studies have elucidated that long non-coding RNA (lncRNA) performs as a pivotal agent in osteosarcoma (OS). Nevertheless, lncRNA long intergenic non-coding 00641 (LINC00641)'s functions in DDP resistance for OS remain obscure. The purpose of this study was to investigate the effect and mechanism of LINC00641 on drug resistance of OS. The tissues of both clinical cancer patients and the normal control were gathered. Detection of LINC00641, microRNA-320d (miR-320d) and myeloid cell leukemia-1 (MCL1) was conducted. After the selection of OS cell lines, the detection of cell advancement was applied. Series of experiments were conducted to verify the interaction of LINC00641, miR-320d and MCL1. Xenografted tumor model in vivo was utilized to determine the function of LINC00641. The data displayed, LINC00641 was prominently elevated in OS tissues and cells, especially in DDP-resistant tumors and cell lines. Knock-down LINC00641 was able to attenuate progression of DDP-resistant OS cells thus dampening their drug resistance toward DDP. Moreover, knock-downing LINC00641 gene was also able to manifest antagonism toward DDP-resistance in vivo . On the grounds of bioinformatics prediction, a direct binding of LINC00641 with miR-320d existed, whose target was MCL1. Meanwhile, LINC00641 modulated MCL1 via targeting miR-320d. Additionally, repressive LINC00641 blocked MCL1 via emulative interaction with miR-320d, thus expediting DDP-sensitivity of OS cells. All in all, it is found that LINC00641 is available to escalate drug resistance of DDP-resistant OS cells via mediation of miR-320d/MCL1 axis. Graphical abstract: uf0001